El ingeniero D. Juan Gabland y White - Guarda, Gabriel (Revista Chilena de Humanidades, 2016)
The author presents a bibliographic checklist relating to John Garland White, an engineer who fulfilled very important tasks in Chile during the second half of the 18th century, all of them connected with military constructions. An Irishman by birth, Garland has been regarded as one of the most highly skilled professionals is his field during the Viceroyal periocl , and there is no doubt that his technical know-how was extremely valuable in the planning and execution of engineering works required by the King of Spain, particularly in the zone around Valdivia.